VERRUCOUS CARCINOMA OF LEFT BUCCAL MUCOSA– A CASE REPORT - Dr. K. Balasankari; Dr. E.Sandhiya; Dr. M.Ashwini; Dr. M. Sehtaj; Dr. M. Arunachalam; Dr. M. Sathish Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Oral verrucous carcinoma accounts for 0.57-16.08% of oral squamous cell carcinoma (SCC) with a 5-year survival rate of only approximately 50%. Verrucous carcinoma is a low-grade variant of squamous cell carcinoma (SCC) with specific morphologic, cytokinetic and clinical features. It is a locally aggressive tumour and does not metastasize to regional lymph nodes or to distant sites. Etiological factors include alcohol consumption, tobacco chewing and other irritants to the oral mucosa such as betel nut chewing, poor oral hygiene, a poorly fitting dental prosthesis and earlier mucosal injuries or scars have also been described as the risk factors in the development of oral verrucous carcinoma. The purpose of this article is to present the histological characteristics of oral verrucous carcinoma in a 50 year old female patient.